Effectiveness of interval training in increasing VO2max in pencak silat athletes - Ali Mardius; Davi Sofyan; Rafid Saad Hadi; Eri Barlian; Nurul Ihsan; Yuni Astuti; Yovhandra Ockta (Sport TK)
This study provides the most recent pertinent insights into the physiological factors influencing aerobic performance training in pencak silat athletes. An athlete's physical capacity is important for success in sports performance. Aerobic capacity is recognized as primary component. The prevailing consensus among authors identifies maximal oxygen uptake VO2max as the best indicator of an organism's aerobic capacity, and a key metric for assessing the physical capacity in pencak silat athletes. Employing a quasi-experimental approach, this research was conducted between July and August 2023. Focusing on 45 pencak silat athletes from Senior High School 1 Basa Ampek Balai Tapan, using purposive sampling, 30 male athletes were selected as participants, with the bleep test used as the primary assessment tool. Statistical analysis via t-test revealed a positive impact of interval training on the VO2max in pencak silat athletes, facilitating enhanced aerobic metabolism and energy production during maximum exertion.